Pengaruh Promosi Dan Saluran Distribusi Terhadap Keputusan Pembelian: Survey Produk Fashion Pada Salah Satu Departement Store di Kota Cimahi - Sipa Sopiani; Irena Larashati; Dudung Juhana; Ester Manik (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2022)
The decline in sales of fashion products in one of the department stores in Cimahi City is the background of this research. So the authors want to know whether there is an influence of promotion and distribution channels on purchasing decisions on fashion products at one of the department stores in Cimahi City. Researchers surveyed customers who had made fashion products that became the object of study. The research method used is path analysis because this research, in addition to getting an overview of purchasing decisions associated with promotions and distribution channels, also gets an overview of the pattern of relationships and the influence of the research variables determined. The study results show a positive relationship between promotion (X1) and distribution channel (X2), 0.826. There is a positive and significant effect of promotion (X1) on purchasing decisions (Y) that is equal to 40.67%; there is a positive and significant influence of distribution channels (X2) on purchasing decisions (Y) of 32.53%. Therefore, there is a positive and significant influence of promotion (X1) and distribution channel (X2) on purchasing decisions (Y) together, which is 73.2%, and the rest by other factors or also called epsilon by 26.8%. These studies stated that improving purchasing decisions can be done by increasing promotion and location.